Knowledge of human papillomavirus vaccines among university students in Angola - Rocha, João Wilson; Vasconcelos, Ana Morais; Simões, Honolfo Elves; Soqui, Elizandra; Rosa, Nilton Helibrando (Brazilian Journal of Oncology, 2022)
Introduction: Cervical cancer is the first most common cancer among women in Angola and accounts for 37.6% of cancers among women in Angola. The human papillomavirus (HPV) is a causative agent of the disease. Recent advances in technology have led to the introduction of vaccines to prevent HPV infection. This study aims to assess the awareness of university students about HPV infection as a causal factor for cervical cancer and their knowledge about HPV vaccination. Assessing knowledge about vaccination among university students helps us to understand the level of awareness about it.Material and Methods: A questionnaire-based study was carried out on 106 university students, from May 10th to July 26th, 2021. The questionnaire consisted of 10 multiple-choice questions and the results were analyzed using percentages.Results: Knowledge about HPV as a causative agent of cervical cancer was found in 84.2% of students. Awareness of the availability of the HPV vaccine was observed in 55.3%. Complete vaccination status was verified in 0% male students and 13% female students. No male students and 13 female students received incomplete vaccination. 33 men and 73 women were willing to be vaccinated with the HPV vaccine.Conclusion: The present study concludes that there is not a good knowledge of university students about cervical cancer and its prevention. There is also little knowledge about the HPV vaccine, meaning the availability of the vaccine, the right age group for vaccination, and the recommended vaccination for men need to be improved. Vaccination status is poor among men and women because it is not on the national vaccination calendar. The desire to get vaccinated in male students was lower compared to female students. Thus, there seems to be a need to motivate male students for vaccination. Therefore, more awareness should be created about the HPV vaccine among students. The government through the Ministry of Health must incorporate the HPV vaccine in the vaccination calendar.
Keywords: Knowledge; Papillomavirus infections; Angola; Faculty; Students; Uterine cervical neoplasms